Examining the Antecedents and Consequences of Employee Engagement on Temporary Agency Workers in a Partner-led Environment - SIAN RODERICK (2023)
The recent Covid-19 pandemic highlighted the increasing reliance of organisations on temporary agency workers (TAWs) to survive in business environments that are characterised as being temporal, unpredictable, and cyclical. Temporary workforces are growing in popularity as it offers flexibility and independence for both employees and the employer (i.e., The Client). At the same time, the recruitment industry has witnessed significant growth and heightened competition to source reliable, high-quality TAWs as this niche cohort of the workforce underpin the successful performance and outcomes of both agency and client.Despite the increasing number of TAWs and their significant contributions to sustaining competitive advantage and economic growth, extant literature on employee engagement of TAWs to date is rather limited. Also, what research does exist is rather limited as seminal research focused on employee engagement of full time employees, rather than any rigorous examination of engagement with TAWs who operate in turbulent and constantly changing ‘real world’ business environments.This study addresses this gap in knowledge by “examining employee engagement from the perspective of the TAWs to identify the influence and implications of job and organisation engagement”. This study draws on an exemplar case study of a well-known large UK retailer (i.e., The Client) that operates a distribution warehouse and employs TAWs who are sourced through three recruitment agencies.A review of seminal literature provides the theoretical base for the antecedents and proposed outcomes of employee engagement to inform the proposed research model to capture the perceptions of TAW engagement at The Client organisation. A self-completion questionnaire was completed by 277 TAWS and the research model was tested using partial least squares structural equation modelling (PLS-SEM) and SmartPLS v.4.The findings challenge two long-held assumptions about employee engagements First, job engagement and organisation engagement are two significantly distinct constructs that have implications for The Client organisation. Second, experiences of employee engagement for TAWs differ from that of traditional employees as they are heavily reliant on The Client organisation’s ability to support, value and embed them into the workforce and wider mission of the organisation.